ՀՀ գյուղատնտեսական նշանակության հողատեսքերի կադաստրային արժեքի որոշման նոր մեթոդիկայի մշակման անհրաժեշտությունը - Հովհաննիսյան, Տիգրան; Էֆենդյան, Պարույր; Ղազեյան, Խաչատուր; Խուդավերդյան, Նանե (ՀԱԱՀ հիմնադրամ)
В результате глобального потепления в нашем регионе произошли климатические изменения, и во многих районах, где из-за неблагоприятных погодных условий долгое время выращивались только традиционные культуры, в настоящее время возделываются нетрадиционные, ценные или нетипичные для данной местности виды. Исследованиями и анализом, проведенными в рамках данной работы, обоснована необходимость разработки новой методики определения кадастровой стоимости земель сельскохозяйственного назначения РА, основанной на расчете рыночной стоимости и чистого дохода земельных участков. As a result of global warming, significant changes in weather patterns have occurred in our region. These changes have led to shifts in agricultural practices, with non-traditional, high-value crops or previously uncultivated crops now becoming more common in areas where traditional crops have been grown for many years, often due to adverse weather conditions. Over the past 25 years, alongside the development of market relations in the Republic of Armenia, the natural properties of agricultural lands, crop productivity, cultivation costs, and the types and distribution of crops have all undergone notable changes. Currently, land tax rates in the Republic are differentiated based on cadastral zones, provinces (marzes), communities, and land-use entities. This study examines and analyzes the evolving agricultural landscape in Armenia, highlighting the need for a new methodology to determine the cadastral value of agricultural land. This proposed methodology would be based on calculating the market value and net income generated from the land.
Keywords: Ագրարային տնտեսագիտություն